Determinant factors affecting the success of Knowledge Transfer Program (KTP) in Malaysia - Rosle Mohidin; Roslinah Mahmud; Lim, Thien Sang; Roselina Ahmad Saufi; Zatul Karamah A.B.U.; Durrishah Idrus; Ahmad Shaharudin Abdul Latip (International Journal of Business and Management Studies, 2019)
Knowledge management is a fundamental requirement for continuous survival of an organization. The involvement of all parties – the government, universities, industries, and communities are crucial to ensure success of knowledge transfer and knowledge creation. In the past, it is shown that the collaborations among academia-university-community had played a significant contribution in developing human capital and the country economy. The Malaysia Plans, Vision 2020 and the New Economy Model inspire the Ministry of Education (MOE) Malaysia to embark on Knowledge Transfer Programme (KTP). Since the inception of KTP in 2010, the collaborations between the Malaysian local universities, industries and communities continue to flourish. As at 2017, there were 460 KT projects implemented in Malaysia by all the 20 public universities. This study aims to investigate the main factors that contribute to the success of KT implementations in Malaysia. This study was conducted with the vision to identify the key factors for knowledge transfer projects’ implementation. The study has outlined Academia Capability dimensions and Knowledge Transfer Mechanism as one of the main factors affecting the KT project performance. In addition, the study has also examined the role of Knowledge Transfer Mechanism as a mediating factor. The study has employed quantitative design and information were collected through questionnaires survey involving academia represented by various local universities that have been granted projects by the KT Centre. Findings of this study has confirmed Academia Capability dimensions have positively and significantly affecting the KT project performance. These findings imply enriching human capital values of academia and strengthening support system are necessary in ensuring the success of a KTP project. The study has also suggested that understanding academia and KT mechanism might be necessary in transferring the knowledge. This further proven that, knowledge transfer process can positively contribute to business and economic development and further sustaining the nation well-being.